Criminal Law Policy in the Framework of Overcoming Criminal Acts of Fraud and Fraudulent Acceptance Based on Justice - Ferari Wiranata, Eddy; Soponyono, Eko (UNISSULA Semarang, 2025)
This study aims to determine and analyze criminal law policies in efforts to overcome criminal acts of fraud and receiving money in current positive law, legal problems that occur in criminal law policies to overcome criminal acts of fraud and receiving money in current positive law, and analyze criminal law policies in order to overcome criminal acts of fraud and receiving money based on justice. The normative legal approach method, analytical descriptive research specifications, the data used are secondary data, the data collection method is with literature study, and the data analysis method is qualitative analysis.The theories used are the Pancasila justice theory and progressive legal theory. Based on the research results, it was concluded that the criminal law policy in efforts to overcome the crime of fraud and receiving money in positive law currently still emphasizes retaliation and the injured victim becomes passive, thus not reflecting justice. This is due to legal problems, namely the formulation of criminal sanctions for fraud and the discussion is still thick on the values of imprisonment, the rights of victims are neglected, does not differentiate between minor and serious crimes, resulting in overcrowded prisons. The criminal law policy in order to overcome the crime of fraud and receiving money based on justice is a restorative justice approach, namely by avoiding imprisonment and prioritizing the obligation to pay compensation to victims of criminal acts, with the condition that there is an agreement between the victim and the perpetrator of the crime. This realizes justice for both victims and perpetrators, where the victim receives compensation for the losses they experience, while the perpetrator is accountable for his actions by providing compensation to the perpetrator of the crime.